Abangan, Kejawen, and the Dream Sellers in Coastal Java - Nely Rahmawati Zaimah; Marita Ika Joesidawati; Fatchiatuzahro; Suwartiningsih; Muhammad Henry Wahyudi (Societas Dei: Jurnal Agama dan Masyarakat)
This study explores the socio-cultural dynamics of Javanese coastal communities, emphasizing the existence of their indigenous traditional beliefs: Javanism (Kejawen) with its unique spirituality and Abangan, which practically reflects Islam in a syncretic form blending Javanese culture and Sufism. The research focuses on six regions: Subang, Cirebon, Pekalongan, Rembang, Tuban, and Pasuruan. Using Spradley’s domain, it examines the spiritual frameworks and practices of Kejawen and Abangan, including distinctive traditions such as mysticism and cultural titles. Participatory observations reveal that Kejawen and Abangan communities continue to preserve their beliefs, actively practising them while shaping a communal identity that strengthens social bonds. Ironically, some deviant practices, such as shamanism, charms for wealth, and occultism, are often associated with these groups. The findings also highlight the critical role of religious moderation in safeguarding traditional practices, addressing misuse of beliefs, and promoting harmony. This study offers valuable insights into the resilience of Javanese culture amidst the dynamics of contemporary society.